PERAN PENTING TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PENDIDIKAN - Rohyadi, Edi; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the important role of information and communication technology in the implementation of education in elementary schools and the impact of the rapid development of ICT. The scope of discussion in this research starts from the definition, role, implementation, and impact of the utilization of information and communication technology in learning in elementary schools. The method used in this research is a literature study, namely collecting and analyzing previous research literature related to information communication technology. The result is that information technology has a significant role in helping the implementation of an innovative learning process. Apart from being a medium, ICT can also be a learning resource for teachers and students in elementary schools. But at the same time there are negative impacts of the development of information and communication technology. So a school teacher has an important role in controlling the use of ICT to positive things only. Therefore, teachers must be equipped with adequate digital literacy skills. The conclusion of this research is that the utilization of information and communication technology in education can enrich the learning experience of students and make the learning process more qualified. The utilization of ICT in education can also form an innovative, creative and competitive generation. In the end, the quality of education in a country can increase.